Towards Selecting Effective Open Source Learning Management System/Software (OSLMS) for Higher Education Domain. (January 2021) - Sk, Md Ajimuddin; Jana, Sibsankar; Khatun, Samima
We are in the age of information and communication technology (ICT), where the learning communities (i.e., learners, teachers, scholars, etc.), mainly in higher education domains, are more technology dependent. The stakeholders always handle advanced research, study and technologies, and therefore they need some authentic and updated information to satisfy their daily needs. They simply need some updating as well as real-time interactive digital learning platforms that can provide fast, authentic and updated information to satisfy their academic needs. This learning platform completely depends on the judicious designing methodologies, and this designing methodology totally depends on the reliable and effective digital learning tools or learning management system (LMS). The present study is an attempt to design the standard process towards selecting an authentic, reliable and effective open source learning management software/system (OSLMS) for the higher education platform. In this regard, the study has been designed in three layers for the selection of the popular and most downloaded OSLMS in the world. Later in the third layer, a comparative study of the final six OSLMSs has been conducted based on the features under various criteria and parameters to select the right one. Lastly, it is found that the Moodle fulfilled most of the criteria and is selected as the most authentic, interactive and trustworthy OSLMS for the higher education system.